2021
DOI: 10.14569/ijacsa.2021.0120408
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Implementation Framework for an Efficient Transformation to Online Education

Abstract: The least developed countries have been tasked with introducing effective e-learning frameworks as they look to overcome technology inadequacies and lack of research support or vision. Ongoing efforts are reliant upon a mixed-methods approach. A systematic literature analysis and a quantitative examination have been undertaken to achieve a thorough assessment of the available data taken from educational facilities in Kuwait. Results show clear support for embracing e-learning, with most participants recognizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is also true of societies within the Gulf Countries Council (GCC), as Internet access and technical access indicate that as egovernment, digital work, and educational activities become more complex, populations with fewer computer skills, in Vol 12 Issue 1 DOI No. : 10.24940/theijbm/2024/v12/i1/BM2401-006 January, 2024 contrast to developed nations, will have greater access to these technologies (Al-Hunaiyyan, Alhajri, Alzayed & Alraqqas, 2016). This is a significant indication of countries' inadequate development potential, and the research also observed that "personal" talents, which transcend technical and fundamental abilities, are becoming increasingly in demand.…”
Section: Integrating the Twenty-first Century Skills Into Education S...mentioning
confidence: 99%
“…This is also true of societies within the Gulf Countries Council (GCC), as Internet access and technical access indicate that as egovernment, digital work, and educational activities become more complex, populations with fewer computer skills, in Vol 12 Issue 1 DOI No. : 10.24940/theijbm/2024/v12/i1/BM2401-006 January, 2024 contrast to developed nations, will have greater access to these technologies (Al-Hunaiyyan, Alhajri, Alzayed & Alraqqas, 2016). This is a significant indication of countries' inadequate development potential, and the research also observed that "personal" talents, which transcend technical and fundamental abilities, are becoming increasingly in demand.…”
Section: Integrating the Twenty-first Century Skills Into Education S...mentioning
confidence: 99%
“…According to (Nutsubidze and Schmidt 2021), most educational institutions encourage their instructors to use online and virtual learning while training them on the use of technology, however, less focus was given to e-content development (Peterson, 2003), as well as issues related to behavioral connection, collaboration, and relationship development amongst instructors as well as between instructors and students (Al-Hunaiyyan, Alhajri, Alzayed, & Alraqqas, 2016). In a successful online learning environment, instructors must consistently participate, communicate effectively, facilitate regular group discussions, and provide students with direction and encouragement.…”
Section: Instructors' Digital Competencies In the Context Of Hrmmentioning
confidence: 99%
“…We must not overlook the development of modern and flexible policies and legislation, which are necessary for such kind of digital transformation, and enable maximum use of information and communication technology in the field of education. There is no doubt that the absence of an integrated system for the application of e-learning at the national level, as well as the absence of scientific standards to measure the efficiency of the various components of digital education, in addition to the absence of an integrated framework for developing the capabilities of teachers to be effective in the digital education environment (Al-Hunaiyyan, Alhajri, Alzayed, & Alraqqas, 2016;Liu, Zhao, & Su, 2022).…”
Section: Instructors' Digital Competencies In the Context Of Hrmmentioning
confidence: 99%
“…HRM supports self-learning initiatives by providing access to resources, tools, and platforms that enable employees to enhance their skills independently (Alainati S. J., 2021A;Alainati S., 2024A). This may involve promoting elearning platforms, offering online courses, or creating a culture that encourages continuous learning (Al-Hunaiyyan et al, 2016;Al-Hunaiyyan et al, 2021D;Al-Huwail et al, 2007). The interconnection HRM and the 21st-century competences of employees and students is profound, as the latter's employability and achievement in the modern workplace are significantly dependent on the former.…”
mentioning
confidence: 99%
“…The value of personnel is critical when considering the domains of online learning delivery and human resources (Alainati et al, 2023B;Alainati et al, 2023C). In online and self-learning environments, HRM is responsible for facilitating and guiding the learning experience for workers, providing feedback and support, and evaluating learners' performance (Al-Hunaiyyan et al, 2021C;Al-Sharhan et al, 2006;Al-Hunaiyyan et al, 2021B;Al-Hunaiyyan et al, 2021A;Alhajri et al, 2017) to ensure that the program meets the learning objectives and equipping workers with 21st century skills (Alainati et al, 2023A;Al-Sharhan et al, 2010;Alainati et al, 2023B), making sure that online training materials accommodate individual differences (Alhajri et al, 2011).…”
mentioning
confidence: 99%